Assessing the Effects of Drought on Livestock Farming Livelihoods in Western Odisha: A Study of Drought and Non Drought Years - , Devi Prasanna Swain; , Arunasis Goswami; , Bhabesh Chandra Das; , Suman Sant; , Birendra Pratap Singh; , Kumar Govil (Archives of Current Research International, 2024)
The irregular climatic variation, which is causing drought, flood, cyclone, etc., across the globe is increasingly affecting the livestock rearing leading to great distress to livestock farmers financially, socially and economically during the above periods [1,2]. Drought is a recurring phenomenon in Western Odisha, posing significant threats to the livelihoods of livestock farmers. This study investigates the effects of drought on the livelihoods of livestock farmers in the region, exploring the socio-economic and environmental implications. A mixed-methods approach was employed, combining surveys, interviews, and focus group discussions with 72 livestock farmers. Results show that drought leads to reduced livestock productivity, decreased income, and diminished food security. Farmers' coping strategies, such as distress sales of assets and migration, exacerbate their vulnerability. The study highlights the need for drought-specific livestock management practices, improved access to credit and insurance, and enhanced extension services to support climate-resilient livelihoods. The study further revealed that animal rearing in the drought affected areas provides a sense of food security, social status and ability to meet the expenses in social rituals. By understanding the impact of drought on livestock farmers' livelihoods, this research aims to inform targeted interventions to enhance their resilience and adaptive capacity. Therefore, the Government of Odisha may initiate serious efforts to promote animal husbandry activities in these districts to support the farmers to negate the adverse impact of drought and to check the distress migration from these districts during the drought period. Policy recommendations include integrating livestock support into drought relief programs and promoting water harvesting and conservation practices.